The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/bem.20650
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of human skin at an acupuncture point in the 50-75 GHz frequency range: A pilot study

Abstract: The reason for using acupuncture points as exposure sites in some applications of millimeter wave therapy has been unclear. Acupuncture points have been suspected to exhibit particular direct current (DC), low-frequency electrical and optical properties compared to surrounding skin. To assess if such a biophysical correlation could exist at millimeter wave frequencies used in the therapy, we investigated the dielectric properties of an acupuncture point on the forearm skin within the 50 -75 GHz range. These pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The levels of emissivity and reflectivity are determined by the relative complex permittivity of a medium, and these have been measured for human skin in the microwave and MMW frequency bands at specific frequencies and over limited number of participants and measurement locations by using an open ended coaxial probe in contact with the human body [22,30,[41][42][43]. Due to the limited measured data, different theoretical models are often used to predict the relative complex permittivity of the skin, such as the Cole-Cole model and Debye model [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The levels of emissivity and reflectivity are determined by the relative complex permittivity of a medium, and these have been measured for human skin in the microwave and MMW frequency bands at specific frequencies and over limited number of participants and measurement locations by using an open ended coaxial probe in contact with the human body [22,30,[41][42][43]. Due to the limited measured data, different theoretical models are often used to predict the relative complex permittivity of the skin, such as the Cole-Cole model and Debye model [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…A half‐space electromagnetic model of the human skin was therefore developed to determine the emissivity of healthy skin and skin having a variety of medical conditions. The reflection coefficients for healthy skin and skin with second degree burns over the band 26.5–40 GHz were taken from Gao and Zoughi [] with open‐ended coaxial probe data from Alekseev and Ziskin [], Egot‐Lemaire and Ziskin [], and Smulders []. Permittivity data were used from the parametric models such as the Cole‐Cole model and Debye model [Gabriel et al, ,; Wallace et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the skin resistance, other electrical properties at acupoints were also discussed. For example, unilateral manual stimulation of acupoints LU7 and Zhaohai ( KD6 ) triggers the increase of skin potential amplitude than no acupuncture group ; volt‐ampere (V‐A) characteristic of acupoints has the characteristics of both nonlinear and inertia, and changes obviously in the patients of heart disease or stomach diseases ; the skin dielectric property of PC4 is different from surrounding nonacupuncture sites in the 50–61 GHz range ; the electrical conductance of most acupoints on Heart Meridian were decreased after EA stimulation in 10 healthy volunteers and varied with pathogenesis . However, a recent review showed that the electrical properties of acupoints were in a condition of imbalance even they have the same name on the affected meridians located symmetrically on bilateral sides of the body .…”
Section: The Local Effects When Stimulating Acupointsmentioning
confidence: 99%